1985
DOI: 10.1007/bf01868733
|View full text |Cite
|
Sign up to set email alerts
|

Transport of neutral and cationic amino acids across the brush-border membrane of the rabbit ileum

Abstract: The transport of sugars and amino acids across the brush-border membrane of the distal rabbit ileum has been studied. The kinetics of the transport of glucose demonstrated that the data obtained with the present technique are less distorted by unstirred layers than those obtained with the same technique adapted to the use of magnetic stirring. The role of depolarization of the electrical potential difference across the brush-border membrane in mutual inhibition between different classes of amino acids was esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 28 publications
5
15
0
Order By: Relevance
“…However, in some studies a cationic amino acid transport activity has been described resembling system y ϩ in nonepithelial cells (357). A number of studies clearly established the presence of a Na ϩ -independent transporter for neutral and cationic amino acids (226,228,229,264). As a result, this transporter has been classified as system b 0,ϩ to indicate its similarity to the system defined in mouse blastocysts (388).…”
Section: Transport Of Cationic Amino Acids and Cystine Across The Apimentioning
confidence: 97%
See 1 more Smart Citation
“…However, in some studies a cationic amino acid transport activity has been described resembling system y ϩ in nonepithelial cells (357). A number of studies clearly established the presence of a Na ϩ -independent transporter for neutral and cationic amino acids (226,228,229,264). As a result, this transporter has been classified as system b 0,ϩ to indicate its similarity to the system defined in mouse blastocysts (388).…”
Section: Transport Of Cationic Amino Acids and Cystine Across The Apimentioning
confidence: 97%
“…System B 0,ϩ is defined as a Na ϩ -dependent high-affinity transporter for neutral and cationic amino acids and was first described in mouse blastocysts (389). A transporter with very similar properties was functionally detected in rabbit distal ileum (226). In an attempt to identify novel neurotransmitter transporters, Sloan and Mager (348) cloned a cDNA from human mammary gland that encoded a transporter of 634 amino acids which had significant sequence homology to brain glycine transporters GLYT1 and GLYT2 (348).…”
Section: The System B 0ϩ Neutral and Cationic Amino Acid Transportermentioning
confidence: 98%
“…The neutral amino acids enter the rabbit jejunal brush border membrane vesicles via three transport routes: non-saturable simple diffusion, Na'hdependent carriers and Na+ -dependent carriers (Stevens et al, 1982(Stevens et al, , 1984Munck, 1985;Harig, 1989). T w o groups of experiments were carried out to determine which L-threonine systems of transport could be affected by EM.…”
Section: Discussionmentioning
confidence: 99%
“…Early results seem to indicate that EM could decrease the L-threonine transport across the mucosal border. It has been demonstrated that .neutral amino acids are transported across the brush border by both Na+dependent and Na+-independent systems of transport (Stevens et al, 1982(Stevens et al, , 1984Munck, 1985;Harig el al., 1989).…”
Section: Effect Of E?ythromycin C M L-threonine Transportmentioning
confidence: 99%
“…Food protein is an essential nutrient needed by the human body for growth and maintenance. Traditionally, it is believed that food proteins are digested in the gastrointestinal tract by enzymes to amino acids, dipeptides, and tripeptides and then absorbed into the enterocyte across the brush‐border membrane via multiple amino acid and peptide transport systems . The absorption of peptides is more efficient than free amino acids .…”
Section: Introductionmentioning
confidence: 99%